2019
DOI: 10.1109/tcsii.2019.2899938
|View full text |Cite
|
Sign up to set email alerts
|

A Compact Adder and Reprogrammable Logic Gate Using Micro-Electromechanical Resonators With Partial Electrodes

Abstract: In this work, the design principles and experimental demonstration of a compact full adder along with a reprogrammable 4 input logic gate are presented. The proposed solution for implementation of digital circuits is based on a clamped-clamped micro-beam resonator with multiple split electrodes, in which the logic inputs tune the resonance frequency of the beam. This technique enables re-programmability during operation, and reduces the complexity of the digital logic design significantly; as an example, for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The digital inputs, which are DC voltages applied to the corner electrodes, modulate the resonance frequency of the beam. For a device with input electrodes separated from the beam by equal air gaps in a previous work [8], simulation and experimental results showed that the combinations that contained the same number of ones/zeros (regardless of their order) had the same effect on the resonance frequency of the beam. For example, the input combinations 0001-0010-0100-1000, which correspond to the decimal equivalent values 1-2-4-8, resulted in almost the same resonance frequency for the beam.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…The digital inputs, which are DC voltages applied to the corner electrodes, modulate the resonance frequency of the beam. For a device with input electrodes separated from the beam by equal air gaps in a previous work [8], simulation and experimental results showed that the combinations that contained the same number of ones/zeros (regardless of their order) had the same effect on the resonance frequency of the beam. For example, the input combinations 0001-0010-0100-1000, which correspond to the decimal equivalent values 1-2-4-8, resulted in almost the same resonance frequency for the beam.…”
Section: Introductionmentioning
confidence: 79%
“…In a previous work [8], we presented a more complicated digital block, namely a full adder, which can be considered as the basic block of all arithmetic operations and digital signal processing. The proposed micro-resonator adder required 2 resonators, which is ~14 times less complex than the conventional optimized CMOS adders.…”
Section: Introductionmentioning
confidence: 99%
“…Run-time re-programmability allows using the same hardware to implement different functions, which can lead to minimizing the overall footprint of the system when using nano-scale resonators. Table 2 compares the number of required CMOS transistors and resonators to implement NOR gate, AND gate, and a full adder [15]. Using electromechanical resonators can reduce digital design complexity by 4 to 14 times compared to traditional CMOS designs.…”
Section: Layout Creation and Post-layout Simulation Inmentioning
confidence: 99%
“…Although micro-scale resonators are bulky in general, nano-resonators can reduce area consumption. For example, the nano-resonator based full adder in [15,16] is 45 times smaller than a CMOS mirror adder in 65nm Technology. In addition to reduced complexity, the proposed micro-resonator based gates are expected to have lower energy consumption due to the absence of direct currents, only switching energy, and AC activation energy are involved as discussed in details in [14].…”
Section: Layout Creation and Post-layout Simulation Inmentioning
confidence: 99%
“…Therefore, a new research direction has emerged focusing on the noncontact mode by employing the dynamic vibration of MEMS and NEMS resonators. In the dynamic mode, the logic states are encoded by activating and deactivating the resonance frequency using different modulation and actuation techniques, such as DC tuning [9], electrothermal tuning [10,11], parametric resonance [12], and frequency mixing [13]. Utilizing different modes of vibration to execute logic operations improves the operation speed of the logic unit and increases the lifetime of the proposed device.…”
Section: Introductionmentioning
confidence: 99%